CD36 deficiency inhibits proliferation by cell cycle control in skeletal muscle cells - Sun, Jingyu; Su, Yajuan; Xu, Yaning; Qin, Duran; He, Qianhui; Qiu, Haiping; Zhuo, Jiatong; Li, Weida (Frontiers in Physiology, 2022)
Obesity-related muscular dysfunction and relative muscle atrophy affect an increasing number of people. The elucidation of molecular mechanisms underlying the skeletal muscle development and growth may help to maintain obese skeletal muscle mass. Fatty acid translocase (FAT/CD36), a long-chain fatty acid transport protein, is crucial for lipid metabolism and signaling. CD36 is known to function in myogenic differentiation, and whether it affects the proliferation of skeletal muscle cells and the underlying mechanisms remain unclear. In this study, the effect of CD36 deficiency on skeletal muscle cell viability and proliferation was examined using C2C12 myoblasts. Results showed that the loss of CD36 inhibited viability and promoted apoptosis in C2C12 myoblasts. Intriguingly, the silencing of CD36 suppressed cell proliferation by preventing the cell cycle from the G0/G1 phase to the S phase in a cyclin D1/CDK4-dependent manner. Overall, we demonstrated that CD36 was involved in skeletal muscle cell proliferation by cell cycle control, and these findings might facilitate the treatment of obesity-related muscle wasting.